Verification and validation of OpenFOAM for high-lift aircraft flows - Ashton, N; Skaperdas, V (American Institute of Aeronautics and Astronautics (AIAA), 2019)
This paper presents a detailed investigation into the performance of the open-source finite volume computational fluid dynamics (CFD) code OpenFOAM for complex high-lift aircraft flows. A range of cases are investigated, including a zero-pressure gradient flat plate, a NACA0012 airfoil at varying angles of attack, a DSMA661 airfoil, a NASA High-Lift Common Research Model, and a Japan Aerospace Exploration Agency (JAXA) standard model (JSM) high-lift aircraft model. The final three cases were computed as part of the third AIAA High Lift Prediction Workshop. For all of these, the same mesh and turbulence model is used to benchmark against the commercial CFD code STAR–CCM+. The paper shows that OpenFOAM using the Spalart–Allmaras model matches the lift and drag coefficient within 3% of the commercial code for all the test cases simulated. For the JSM high-lift aircraft for which experimental data is available, both codes show good agreement at prestall angles of attack but fail to capture the location of separation at poststall angles, even though the global lift appears to be well predicted. Although OpenFOAM demonstrated comparable accuracy to a range of CFD codes for these aforementioned test cases, further work is required to improve the robustness and stability of OpenFOAM for these types of flows.